2021
DOI: 10.1021/acs.analchem.1c04088
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Noninvasive Quantification of Capsid Gene Filling Level Using Water Proton Nuclear Magnetic Resonance

Abstract: The present work reports an enabling novel technology for quantifying the gene content in adeno-associated viral capsids. The method is based on the water proton nuclear magnetic resonance (wNMR) technique. Instead of analyzing the capsid directly, it utilizes water molecules to distinguish empty and full capsids, as water interacts with them differently. The transverse relaxation rate of water protons, R 2 ( 1 H 2 O), readily distinguishes empty and full capsids and is capable of quantifying the fraction of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Furthermore, the turbidity of the sample does not influence the sample analysis. To date, it has been utilized in numerous biopharmaceutical-related studies, such as to investigate the gene filling of adeno-associated viral capsids, monitor vaccine adjuvant filling level, and sedimentation kinetics, in addition to the inspection of biologic product vials. With respect to proteins, w NMR has been used to monitor the oxidation of a mAb in real time, as well as to obtain information about solution protein concentration under both static and flow conditions, with sensitivity shown to concentrations as low as 0.4 mg mL –1 . Taraban et al have also demonstrated that R 2 ( 1 H 2 O) is sensitive to protein aggregates with a size smaller than 0.45 μm and showed that it was capable of outperforming SEC, DLS, and microflow imaging .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the turbidity of the sample does not influence the sample analysis. To date, it has been utilized in numerous biopharmaceutical-related studies, such as to investigate the gene filling of adeno-associated viral capsids, monitor vaccine adjuvant filling level, and sedimentation kinetics, in addition to the inspection of biologic product vials. With respect to proteins, w NMR has been used to monitor the oxidation of a mAb in real time, as well as to obtain information about solution protein concentration under both static and flow conditions, with sensitivity shown to concentrations as low as 0.4 mg mL –1 . Taraban et al have also demonstrated that R 2 ( 1 H 2 O) is sensitive to protein aggregates with a size smaller than 0.45 μm and showed that it was capable of outperforming SEC, DLS, and microflow imaging .…”
Section: Introductionmentioning
confidence: 99%